Sub-prosthesis stomatitis in patients of Area VI. Cienfuegos. 2015-16 - María Julia Vázquez Vega; Ricardo Aguiar Sanabia; María de los Reyes González Ramos; Ricardo Aguiar Vázquez (Medisur)
Foundation: sub-prosthesis stomatitis leads patients with prostheses to attend a dental consultation frequently. Their management by the health personnel, sometimes, is not adequate, since not all the risk factors that predispose to the disease are evaluated. Objective: to describe risk factors that can affect the appearance of subprosthesis stomatitis. Methods: descriptive cross-sectional study conducted in the Dentistry Department of Area VI Polyclinic, Cienfuegos, from January 2015 to December 2016, which included 59 patients with stomatitis sub-prostheses. To determine the degree of injury, an observation of the oral cavity was made. The variables were analyzed: age, sex, degree of the lesion, type of base of the prosthesis, location of the lesion, as well as risk factors for the onset of the disease. Results: as age progressed, there was a higher incidence of the disease; the female sex was the most affected, with predominance of grade I. Most patients maintained a continuous use of the prosthesis and the most affected were those who carried prosthesis with acrylic base. The greatest number of lesions was located in the middle zone. Deficient oral hygiene, prosthetic and continuous use of the prosthesis, played a fundamental role in the onset of the disease. Conclusions: poor oral and prosthetic hygiene continuous use of the appliance, as well as the presence of unbalanced prostheses, constituted the main risk factors which predisposed to the appearance and worsening of the sub-prosthesis stomatitis.